Electroencephalographic Recordings During Withdrawal of Life-Sustaining Therapy Until 30 Minutes After Declaration of Death. (28th October 2016) - Norton, Loretta; Gibson, Raechelle M.; Gofton, Teneille; Benson, Carolyn; Dhanani, Sonny; Shemie, Sam D.; Hornby, Laura; Ward, Roxanne; Young, G. Bryan
Abstract: Background: The timing of the circulatory determination of death for organ donation presents a medical and ethical challenge. Concerns have been raised about the timing of electrocerebral inactivity in relation to the cessation of circulatory function in organ donation after cardio-circulatory death. Nonprocessed electroencephalographic (EEG) measures have not been characterized and may provide insight into neurological function during this process. Methods: We assessed electrocortical data in relation to cardiac function after withdrawal of life-sustaining therapy and in the postmortem period after cardiac arrest for four patients in a Canadian intensive care unit. Subhairline EEG and cardio-circulatory monitoring including electrocardiogram, arterial blood pressure (ABP), and oxygen saturation were captured. Results: Electrocerebral inactivity preceded the cessation of the cardiac rhythm and ABP in three patients. In one patient, single delta wave bursts persisted following the cessation of both the cardiac rhythm and ABP. There was a significant difference in EEG amplitude between the 30-minute period before and the 5-minute period following ABP cessation for the group, but we did not observe any well-defined EEG states following the early cardiac arrest period. Conclusions: In a case series of four patients, EEG inactivity preceded electrocardiogram and ABP inactivity during the dying process in three patients. Further study of the electroencephalogram during the withdrawal of life sustaining therapies will add clarity to medical, ethical, and legal concerns for donation after circulatory determined death. RÉSUMÉ: Enregistrements électroencéphalographiques pendant le retrait du maintien des fonctions vitales et jusqu'à 30 minutes après la constatation du décès. Contexte: Le moment de la détermination circulatoire de la mort à des fins de don d'organes présente un défi médical et éthique. Des préoccupations ont été soulevées concernant le moment de l'inactivité électrocérébrale en relation à l'arrêt de la fonction circulatoire dans le contexte de don d'organes après la mort cardio-circulatoire. Les mesures électroencéphalographiques (EEG) brutes n'ont pas été caractérisées et pourraient fournir des indices sur la fonction neurologique pendant ce processus. Méthodologie: Nous avons analysé des données électrocorticales en relation à la fonction cardiaque après le retrait du maintien des fonctions vitales et dans la période postmortem, après l'arrêt cardiaque, chez 4 patients hospitalisés dans une unité canadienne de soins intensifs. Nous avons recueilli le tracé EEG sous la lisière des cheveux et la surveillance cardio-circulatoire incluant l'électrocardiogramme, la tension artérielle (TA) et la saturation en oxygène. Résultats: L'inactivité électrocérébrale a précédé la cessation du rythme cardiaque et de la TA chez 3 patients. Nous avons observé une différence significative de l'amplitude de l'EEG entre la période de 30 minutes avant et la période de 5 minutes après l'arrêt de la TA dans ce groupe de patients, mais nous n'avons pas observé d'état bien défini à l'EEG immédiatement après l'arrêt cardiaque. Conclusions: Chez une série de 4 patients, l'inactivité à l'EEG a précédé l'inactivité électrocardiographique et l'arrêt de la TA pendant le processus de la mort chez 3 patients. Des études ultérieures sur l'électroencéphalogramme pendant le retrait du maintien des fonctions vitales aideront à clarifier les préoccupations médicales, éthiques et légales concernant le don d'organes après la détermination circulatoire de la mort.